Inter-relationship Between Malaria Parasitaemia And Widal Reaction In Febrile Patients (Journal of Biomedical Investigation, 2007)
The inter-relationship between malaria parasitaemia and widal reaction in febrile patients was investigated. Malaria and typhoid fever (febrile illnesses) were diagnosed by microscopic malaria parasite presence and Salmonella typhi/paratyphi antibodies screened by Widal reaction with titres greater than or equal to 160 regarded as positive. Of the 797 blood samples investigated. 125 (15.7%) were strictly malaria cases, 429 (53.9%) were mixed infection. 183 (23.0%) were strictly typhoid cases while 60 (7.5%) were negative for both febrile conditions. A co-infection rate of 52.7% and 58.9% was obtained for Salmonella typhi 'O' and 'H' respectively and this was closely followed by S. paratyphi B'O' with a co-infection rate of 41.3%. This positivity rate of S. paratyphi B'O' is significant (P
Keywords: Malaria parasitaemia; Widal test; Paratyphi antigens